INCLUZIUNEA SOCIOEDUCAȚIONALĂ A COPIILOR CU DIZABILITĂȚI - CEBANU, bibliotecară, Filiala „Ovidius”, Victoria (BIBLIOPOLIS, 2020)
The “Ovidius” Library is a public space for community, which provides quality, unrestricted access to information and promotes national and universal values for the entire society. In this context the idea of providing a new service for institutions with closed regime (auxiliary schools, boarding schools) and opening its doors to people from disadvantaged areas of these institutions came by itself. Persons of this category are faced by limited opportunities to participate with others in the community life. Therefore, the inclusion is more than a demagogic or declarative speech, it can be implemented through concrete techniques and teaching strategies based on cooperation, and the librarian can boost processes of social interaction. The “Ovidius” Library by the project Together we know more, with the target group mentally handicapped children from the auxiliary boarding school no. 5 of the capital, has become a bridge for socializing children through the library activities. During the project they were organized a series of activities in order to communicate with others and inform them in some useful things. Among the proposed activities are the literary readings. For children with mental disabilities this kind of activity is the best because it is available and are developmentally appropriate. The suite of held activities and performances were dedicate to the Romanian writers Ion Creangă and Dumitru Matcovschi. The socialization of children with disabilities requires inclusion of traditional library services, to involve students in various library activities, to develop collaborative relationships with other organizations, to support their needs and problems, to contribute to positive community attitudes towards these children.